Konstruksi Maskulinitas dalam Penari Balian Bawo Dayak Deah - Ikeh, Tri Sulapmi Dolina; Priyatna, Aquarini; Adji, Muhammad (UI Scholars Hub, 2020)
Balian Bawo dancer is an important figure in the traditional ceremony of the Dayak Deah tribe. A Balian Bawo is believed to be the link between humans and spirits. This dance should only be performed by a man. One representation of Dayak life is presented in the body of the dancer. This study has a qualitative design and examines the representation of masculinity that is manifested in the body of Balian Bawo dancers. Data collection was conducted by compiling photo and video documentation which was then analyzed using the theory of denotation semiotics and Roland Barthes connotations. The results of the analysis show that the representation of masculinity is manifested through the attribution of clothing that features an open chest, a large bracelet that connotes strength and the use of special space that underlies Balian Bawo dancers. The dominance of masculinity is also manifested through female companions who play a role in preparing all the needs of a Balian Bawo.